Pathogenicity of entomopathogenic fungi isolated from Periplaneta americana against Dolichoderus sp. (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rosa E, Damayanti RD, Yuswantoro J, Indra RN, Oktariana P, Mardianto MFF, Arifiyanto A. 2022. Pathogenicity of entomopathogenic fungi isolated from Periplaneta americana against Dolichoderus sp.. Biodiversitas 23: 5461-5468. Dolichoderus sp. was found to cause a problem for plants, buildings, and households. Many efforts have been made to regulate such animals, but they have not always been successful. Biological control has gained significance in studies as an alternative to chemical control, in which fungi and nematodes are among the successful microorganisms in managing insects. This study aimed to understand the toxicity impact of cockroach-entomopathogen against Dolichoderus sp. Isolated entomopathogens were then administrated to Dolichoderus sp. colonies under laboratory conditions to assess their mortality efficiency. The fungal suspension was sprayed on the ant colonies with concentrations of 107, 108, and 109 conidia/mL. Aspergillus carbonarius KIF3, and Penicillium sp. KIF4 were identified as entomopathogenic fungi. In this investigation, 15 individuals of Dolichoderus sp. were employed in each treatment, with three replications. Pure distilled water with 1% molasses and 0.1% Tween 80 was used as a positive control, whereas sterile distilled water was used as a negative control. The result showed that the entomopathogenic fungus Aspergillus carbonarius KIF3 significantly affected mortality in black ants when administered 109 conidia/mL conidial suspension. It was also observed that the presence of the Dolichoderus sp. population in nature is often associated with mealybugs. There is an opportunity to use an ecological control approach in black ant populations by utilizing entomopathogenic fungi.